RAB39A: a Rab small GTPase with a prominent role in cancer stemness. (10th April 2018) - Chano, Tokuhiro; Avnet, Sofia
Abstract: RAB39A is a Rab small GTPase that localizes at distinct subcellular compartments and regulates intracellular membrane trafficking pathways in vertebrate cells. RAB39A interacts with various molecules and modulates vesicular trafficking that regulates multiple biological pathways such as neuronal differentiation and/or autophagy. Among these pathways are Hippo and Notch signallings, microtubular organization and mitophagy/autophagy. Although RAB39A has never been studied in cancer biology, it has been recently shown to promote cancer stemness and tumorigenesis. Molecular pathways regulated by RAB39A are transcriptionally maintained by the formation of molecular complex with RXRB, NCOR and HDAC that also contribute to cancer stemness. In this review, we provide current knowledge on the oncogenic function of RAB39A and summarize the effect of different microenvironments on RAB39A activity and subcellular localization in cancer cells.